The relationship between family income level, Emotional Intelligence, and Kiasuism among UTAR Undergraduates - Ang, Wei Yee; Choy, Yee Ling; Nurhamizah, Md. Saliman (2019)
The education system in Malaysia contributes to the institutional pressure and competitive school environment. For instance, when a student’s success was determined by their academic performance, they are motivated to be kiasu. However, the phenomena of kiasu behavior is not well understood. Therefore, this study aims to explore how Malaysian undergraduates’ kiasu behavior is influenced by their family income level and emotional intelligence (EI). Based on past findings, we hypothesized that people who have lower EI and higher family income level will have higher level of kiasuism. A total of 358 UTAR undergraduates responded to an online survey consisting of the Emotional Intelligence Scale (EIS) and Kiasu Measure 2.1. Family income level was recorded in the demographic information. Correlation analysis reported positive relationships between subscales of EI (self-awareness, self-regulation, motivation, empathy, & social skills) and kiasuism. Multiple regression analysis indicated that none of the predictors has an impact on kiasuism. The current study fill in the research gap by further confirms that family income level and emotional intelligence does not predict kiasuism significantly. It also provides a foundation for a variety of directions for future research. Future research can be conducted to explore the cultural differences that might exists for socioeconomic status, level of emotional intelligence and kiasuism.